The role of potassium ion channels in chronic sinusitis - Ding, Changhui; Gai, Senxi; Ma, Zhiyong; Yang, Lizhuo; Fu, Zhijie (Frontiers in Pharmacology, 2024)
Chronic sinusitis is a common inflammatory disease of the nasal and sinus mucosa, leading to symptoms such as nasal congestion, runny nose, decreased sense of smell, and headache. It often recurs and seriously affects the quality of life of patients. However, its pathological and physiological mechanisms are not fully understood. In recent years, the role of potassium ion channels in the regulation of mucosal barrier function and inflammatory cell function has received increasing attention. In chronic sinusitis, there are often changes in the expression and function of potassium channels, leading to mucosal damage and a stronger inflammatory response. However, the related research is still in its early stages. This article will review the role of the potassium channel in the pathological and physiological changes of chronic sinusitis. The studies revealed that BK/TREK-1 potassium channel play a protective role in the nasal mucosal function through p38-MAPK pathway, and KCa3.1/ Kv1.3 enhance the inflammatory response of CRS by regulating immune cell function, intracellular Ca 2+ signaling and ERK/MAPK/NF-B pathway. Because ion channels are surface proteins of cell membranes, they are easier to intervene with drugs, and the results of these studies may provide new effective targets for the prevention and treatment of chronic sinusitis.